ANALISIS KOREKSI FISKAL PADA BIAYA RESEARCH AND DEVELOPMENT (STUDI KASUS PT X TAHUN 2014) - Hadining Kusumastuti; Ari Warli Ruchiyat (Program Pendidikan Vokasi Universitas Indonesia, 2020)
This paper discusses the Analysis of Fiscal Correction in Research & Development Costs that occurred in 2014 through a case study of PT.X. In this case, there are differences in interpretations that occur between Taxpayers and the Fiscal Authority on provisions that regulate costs that can be charged to the company, causing tax disputes. Based on the analysis that has been carried out related to tax disputes that occur between PT. X and Tax Officer. The tax dispute that arises against Research & Development Costs is because the cost according to the Fiscal is irrelevant.